An In Vitro Comparative Study of the Push-out Bond Strengths of Various Endodontic Sealers to Radicular Dentin - Mohamed Abdelaziz El Sayed; Safiya Saeed Alderei (Indian Journal of Dental Research)
Background: The bond strength of an endodontic sealer to the root dentin is an important factor in maintaining the integrity of the root canal seal. The present study aimed to assess the push-out bond strength of three endodontic sealers used with the single-cone obturation technique. Materials and Methods: The root canals of 40 central maxillary incisors were instrumented using ProTaper Universal NiTi rotary files. The roots were divided into 4 groups (N = 10) according to the type of root canal sealers: Group 1 (control group): AH Plus/Gutta-percha lateral condensation technique (LC); Group 2: AH Plus/Gutta-percha single-cone technique (SC); Group 3: GuttaFlow 2/SC; Group 4: Realseal SE/SC. After obturation, each tooth was prepared for push-out assessment. The total and sectional push-out bond strengths were measured and statistically analysed. Furthermore, failure modes were identified microscopically. Results: The results indicated that samples in the first group showed the highest total and sectional bond strengths. Samples from other groups showed statistically similar total bond strengths. The highest sectional bond strength was found mainly in the apical root sections. Cohesive failure was predominant for the first group, whereas adhesive failure was predominant in the other groups. Conclusions: It could be concluded that the dentin bond strengths of the tested sealers used with the single-cone technique were nearly similar but lower than those of AH Plus/LC. The highest sectional bond strength was observed in the apical thirds. The failure mode was mostly cohesive for AH Plus/LC and adhesive for sealers used with the single-cone obturation technique.